EKSPLORASI ETNOMATEMATIKA KONSEP GEOMETRI PADA KUE APANG MAKANAN TRADISIONAL SUKU BUGIS - Sutra, Sutra; Nur, Fitriani; Yuliany, Nur (Program Studi Pendidikan Matematika, 2025)
This study aims to explore the ethnomathematics concepts in Apang, a traditional cake of the Bugis people, focusing on applying geometric concepts and cultural values embedded in its production and presentation processes. Using an ethnographic approach, data were collected through observation, interviews, and documentation. The results show that Apang incorporates geometric plane concepts, such as triangles and rhombuses, as seen in the shape and molds of the cake. Additionally, the steaming vessel for Apang is cylindrical with a conical lid, reflecting the application of solid geometry in traditional tools. Apang also embodies the cultural values of the Bugis community, including togetherness, simplicity, gratitude, and patience. It is often served during traditional events such as thanksgiving ceremonies, Menre Bola Baru, and Ramadan traditions. Thus, this study not only reveals the application of mathematical concepts in daily life but also enriches the understanding of the interaction between culture and mathematics within the Bugis community.